Pengembangan LKPD Elektronik melalui Model Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik (Studi pada Materi Pokok Larutan Elektrolit dan Non Elektrolit) - Dwiputri, Ulfa; Salempa, Pince; Sugiarti, Sugiarti (Chemistry Education Review (CER), 2022)
This study is a development research that aims to develop electronic LKPD through adiscovery learning model assisted by the 3D PageFlip Professional application on electrolyte and non-electrolyte solution materials that are valid, practical, and effective to be used to improve students' critical thinking abilities. The research procedure employed the ADDIE development model, which consisted of the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The electronic LKPD was validated by two experts. Then it was tested to grade X Aljabar UPT SMAN 11 Pangkep through Google Meet. The results show that the developed electronic LKPD is valid with an average validity value of 3.42. The practicality test includes: (1) the implementation of LKPD learning through discovery learning model is at an average value of M = 1.96 in the value interval (1.5 ≤ M ≤ 2.0) meaning that the aspects and criteria observed are in fully implemented category, (2) the students gave a positive response with a total average percentage of 77.38%, which means the electronic LKPD is in practical category and (3) the teacher gave a positive response with an average total score of 86.18%, it is invery practical category. The electronic LKPD through the discovery learning developed also meets effective criteria with the test results of each indicator of students' critical thinking abilities is in the percentage of 60% - 80% in medium category.